Influence of prenatal and early-life exposures on food allergy and eczema in infancy: a birth cohort study - Xiao Gao; Yan Yan; Guangyu Zeng; Tingting Sha; Shiping Liu; Qiong He; Cheng Chen; Ling Li; Shiting Xiang; Hongyan Li; Shan Tan; Qiang Yan (BMC, 2019)
Abstract Background Few prospective birth cohort studies are available on the effects of prenatal and early-life exposures on food allergy and eczema among Chinese children. The aim of this study was to evaluate the influence of prenatal and early-life exposures on food allergy and eczema during the first year of life in a prospective birth cohort study. Methods This study was based on a prospective, observational birth cohort of 976 mother-child pairs in three Streets in Changsha, China from January to December 2015. Data on prenatal, early-life exposures and allergic outcomes were obtained from questionnaires collected at birth, and 1, 3, 6, 8, and 12 months of age. Multivariate logistic regression models were performed to estimate the effects of prenatal and early-life exposures on food allergy and eczema. Results Common risk factors for food allergy and eczema in infancy were parental history of allergy, while moderate eggs consumption (3-4 times/week) during pregnancy was protective for both of them compared with low consumption (≤ 2 times/week). Factors only associated with food allergy were maternal aquatic products consumption during pregnancy, number of older siblings and age of solid food introduction, whereas factors only associated with eczema were maternal milk or milk products consumption during pregnancy, maternal antibiotic exposure during pregnancy, season of birth and antibiotic exposure through medication during the first year of life. Conclusion Our study suggests that factors associated with food allergy and eczema are multifaceted, which involving hereditary, environmental and nutritional exposures. Furthermore, differential factors influence the development of food allergy and eczema in infants.